Influência da angulação e desajuste vertical na avaliação de microdeformações ao redor de implantes - Rodrigues, Vinícius Anéas [UNESP]; Tribst, João Paulo Mendes [UNESP]; Santis, Leandro Ruivo de [UNESP]; Lima, Dimas Renó de [UNESP]; Nishioka, Renato Sussumu [UNESP] (Editora Cubo, 2017)
Objective: This in vitro study was to evaluate micro strains around of implant, under the influence of angulations and vertical misfit in three-element implant-supported fixed partial dentures during axial loading by using strain gauge analysis. Material and Methods: Three external hexagon implants with straight configuration and three external hexagon implants with angled (17°) configuration were inserted into two polyurethane blocks. To measure micro strain, four strain gauges were bonded onto the surface of each block. Plastic copings were adapted to a standard wax pattern and cast. An axial load of 30 kgf was applied on the center of each implant for 10 seconds, using a load application device. The vertical misfit was measured at six different points by using a stereo microscope with 100-X magnification. Results: The results showed that the values for different implant angulations were significant (P = 0.0086). The Pearson’s correlation test between micro-strain and vertical misfit revealed no correlation between angled configuration (P = 0.891) and straight configuration (P = 0.568). Conclusion: The micro strain was higher for angled implants; no correlation was found between the vertical misfit and the strain values.
Influence of angulation and vertical misfit in the evaluation of micro-deformations around implants
Keywords: Biomechanics; Dental implants; Dental prosthesis